Oxygen-deficient photostable Cu2O for enhanced visible light photocatalytic activity. Issue 13 (15th March 2018) - Singh, Mandeep; Jampaiah, Deshetti; Kandjani, Ahmad E.; Sabri, Ylias M.; Della Gaspera, Enrico; Reineck, Philipp; Judd, Martyna; Langley, Julien; Cox, Nicholas; van Embden, Joel; Mayes, Edwin L. H.; Gibson, Brant C.; et al.
Abstract : Large-scale synthesis of O-deficient Cu2 O with outstanding visible photoactivity is shown. Abstract : Oxygen vacancies in inorganic semiconductors play an important role in reducing electron–hole recombination, which may have important implications in photocatalysis. Cuprous oxide (Cu2 O), a visible light active p-type semiconductor, is a promising photocatalyst. However, the synthesis of photostable Cu2 O enriched with oxygen defects remains a challenge. We report a simple method for the gram-scale synthesis of highly photostable Cu2 O nanoparticles by the hydrolysis of a Cu(i )-triethylamine [Cu(i )–TEA] complex at low temperature. The oxygen vacancies in these Cu2 O nanoparticles led to a significant increase in the lifetimes of photogenerated charge carriers upon excitation with visible light. This, in combination with a suitable energy band structure, allowed Cu2 O nanoparticles to exhibit outstanding photoactivity in visible light through the generation of electron-mediated hydroxyl (OH˙) radicals. This study highlights the significance of oxygen defects in enhancing the photocatalytic performance of promising semiconductor photocatalysts.